Clusters, orders, and trees: methods and applications : in honor of Boris Mirkin's 70th Birthday - Goldengorin, Boris; Pardalos, Panos M.; Aleskerov, Fuad (Springer Optimization and Its Applications, 2014)
The volume is dedicated to Boris Mirkin on the occasion of his 70th birthday. In addition to his startling PhD results in abstract automata theory, Mirkin's ground breaking contributions in various fields of decision making and data analysis have marked the fourth quarter of the 20th century and beyond. Mirkin has done pioneering work in group choice, clustering, data mining and knowledge discovery aimed at finding and describing non-trivial or hidden structures-first of all, clusters, orderings, and hierarchies-in multivariate and/or network data. This volume contains a collection of papers reflecting recent developments rooted in Mirkin's fundamental contribution to the state-of-the-art in group choice, ordering, clustering, data mining, and knowledge discovery. Researchers, students, and software engineers will benefit from new knowledge discovery techniques and application directions.